RANCANGAN SISTEM INFORMASI AKUNTANSI DENGAN PENDEKATAN PROSES BISNIS DAN COSO: STUDI KASUS PADA PERUSAHAAN ASURANSI JIWA XYZ - Johanes Johanes; Suzanna Lamria Siregar (JURNAL ILMIAH EDUNOMIKA, 2023)
The Accounting Information System (AIS) is a subsystem of the Management Information System (MIS). AIS processes transactions related to financial and non-financial data. AIS can also be interpreted as a tool that regulates the overall course of business from upstream to downstream in a company, every part of the insurance company requires an AIS for the decision-making process. One company that has a strong interest in AIS is a life insurance company. Life insurance companies have very complex information. This very complex analysis is due to the different policy periods and insurance benefits according to product and age, so calculations with various models and formulas are needed. The information can be categorized as premiums, claims, underwriting, investment, profitability, technical reserves based on actuary calculations. Based on the results of the analysis and design of the accounting information system for the underwriting cycle, actuarial, technical reserves, and investment already have a separate system in each part, this is considered less effective and efficient, because on the other hand the information and communication system allows company employees to obtain and exchange required information for the continuity of the existing business. Without the use of a management accounting system, the decision-making process has also been confirmed to be manual, this is considered very ineffective and efficient where when the process is running there must be obstacles from internal parties, and the manual reporting process will take up the available time.